2017
DOI: 10.1088/1752-7163/aa795d
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of volatile propofol to breathing circuit tubing

Abstract: Propofol in exhaled breath can be measured and may provide a real-time estimate of plasma concentration. However, propofol is absorbed in plastic tubing, thus estimates may fail to reflect lung/blood concentration if expired gas is not extracted directly from the endotracheal tube. We evaluated exhaled propofol in five ventilated ICU patients who were sedated with propofol. Exhaled propofol was measured once per minute using ion mobility spectrometry. Exhaled air was sampled directly from the endotracheal tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Moreover, propofol concentration sampled directly from the endotracheal tube was substantially higher than at the expiratory end of the breathing circuit. 11 Additionally, propofol absorption depends on the material itself: silicone, polyurethane and tygon absorb virtually the entirety of volatile propofol, while, in contrast, perfluoralkoxy and polytetrafluorethylene only absorb a negligible amount. 5 Therefore, the larger inner surface area using both lumens during double-lung ventilation possibly explains lower volatile propofol concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, propofol concentration sampled directly from the endotracheal tube was substantially higher than at the expiratory end of the breathing circuit. 11 Additionally, propofol absorption depends on the material itself: silicone, polyurethane and tygon absorb virtually the entirety of volatile propofol, while, in contrast, perfluoralkoxy and polytetrafluorethylene only absorb a negligible amount. 5 Therefore, the larger inner surface area using both lumens during double-lung ventilation possibly explains lower volatile propofol concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Lorenz et al demonstrated that propofol reversibly binds to plastic tubes and breathing circuits, exhibiting saturation kinetics. Moreover, propofol concentration sampled directly from the endotracheal tube was substantially higher than at the expiratory end of the breathing circuit 11 . Additionally, propofol absorption depends on the material itself: silicone, polyurethane and tygon absorb virtually the entirety of volatile propofol, while, in contrast, perfluoralkoxy and polytetrafluorethylene only absorb a negligible amount 5 .…”
Section: Discussionmentioning
confidence: 97%
“…Lorenz at al. demonstrated the behavior of propofol in breathing circuits in an ICU setting where propofol was outgassed from the breathing circuit for hours and remained at 2.8 ppb after 60 h of washing out [ 23 ]. In laboratory studies, perfluoroalkoxy alkanes (PFA) have been identified as materials with low adsorption of propofol [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this effect may be the adhesion of ciprofol to the internal surfaces of the gas generator and the UV-TOFMS. [29][30][31] All of these surfaces have the potential to contribute to carry over. The interaction of gaseous ciprofol with plastic and stainless-steel surfaces should be further investigated.…”
Section: Papermentioning
confidence: 99%